CURRENT UNDERSTANDING IN THE ROLES OF WNT/RYK SIGNALING IN DEVELOPMENT AND HOMEOSTASIS - Wijaya, Natalie Chandra; Suryadi, Jimmy; Yulandi, Adi (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2025)
Wnt/Ryk signaling represents a critical yet underexplored branch of the Wnt pathway, with significant roles in embryonic development and tissue homeostasis. While canonical Wnt/β-catenin signaling has been extensively studied, emerging research highlights Ryk as a key noncanonical Wnt co-receptor influencing processes such as convergent extension, organogenesis, stem cell regulation, and inflammation. Wnt/Ryk signaling mediates diverse cellular outcomes through interactions with ligands like Wnt5a and Wnt11 and exhibits complex crosstalk with canonical pathways. Its dysregulation has been linked to developmental disorders, neurodegenerative diseases, and cancer progression. This review summarizes current insights into Wnt/Ryk function during development and homeostasis, highlights its relevance in human health, and identifies open questions regarding its molecular mechanisms and therapeutic potential. A deeper understanding of this pathway may offer novel strategies for regenerative medicine and targeted treatments for Wnt-related diseases.